Studying process variables to obtain undisturbed shaped soft meat for people with poor oral health. (December 2022) - Grau, Raúl; Hernández, Sergio; Verdú, Samuel; Barat, José M.; Talens, Pau
Abstract: This study evaluated injection (I) and vacuum impregnation (VI) as the best methods to apply papain, and other important processing conditions (batch, aging and cooking conditions), to obtain soft meat (suitable for people with poor oral health) without disturbing its original shape. Two aging times were evaluated and four cooking conditions by immersion in soup. Meat samples were injected or vacuum-impregned (0.85 kPa) with a papain solution (5% w / v ). After cooking, they were analyzed by the compression test, and by image and sensory analyses. The results indicated that by using both methods to apply the enzyme, the obtained meat was suitable for people with poor oral health, even if VI was the better method because it minimized the factors batch, aging and cooking condition. Therefore, the best meat processing method to obtain panelists' highest softness values and the best appreciation was employing aged meat pretreated by VI and cooked at 65 °C for 10 min. Highlights: The enzymatic pre-treatment and cooking combination considerably increase the meat tenderness Vacuum impregnation is the best technique to incorporate enzymes into the thawed cut meat Low temperature; enough to cook meat and accelerate enzyme activity VI + papain + low cooking temperature to reach very tender meat with its original shape Not all commercial meat cuts, of the same tray, aging equally